التَّضْمِينُ عِنْدَ ابنِ فَرْحُونِ المَدَنِي فِي كِتابِهِ(العُدَّة فِي إِعْرابِ العُمْدَة) - سعيد, هاوكار عبد الرحمن (Sulaimani Journal for Humanities, 2022)
In this research, we dealt with the topic of embedding, a topic that we find in linguistic books and books on the analysis of the Qur’an and hadiths. Therefore, we studied this phenomenon according to one of the prominent figures in the Arabic language, which is (Ibn Farhoun Al-Madani) in his book (Al-uddah fi I’rab Al-Umdah). In this book, Ibn Farhoun used embedding as a manifestation of tafsir, in order to reconcile modern texts with grammar. He made a great effort in translating this book, and put his fingerprints on it. He conveyed and discussed the opinions of the grammarians, and expressed his opinion with all boldness and impartiality. In our research, we followed the descriptive analytical approach. The importance of this research lies in the fact that it reveals an encyclopedic personality in language, grammar, grammar and hadith, a scholar who has his own opinions and peculiarities in language, who does not adhere to the opinions of the predecessors.